(untitled) (Cadernos de Sociomuseologia, 2021)
In this paper, I introduce part of my academic-activist trajectory from a biomitography (Lorde, 1984) of “escrevivências” (Evaristo, 2007). With that, I present the crossing of my own political practices linked to my research practices as a museum professional and Sociomuseology activist. By establishing an approximation of the New Museology movement, of LGBT Museology, as well as of a museology permeated by the (in) visibility of narratives, memories and cultural heritage claimed by sexually dissident black women, I intend to articulate a territory of epistemic dispute for the nomination of a Black Lesbian Museology. Keywords: Biomitography, Escrivivências, Sociomuseology, LGBT Museology, Black Lesbian Museology.